Molecular evidence of tick-borne hemoprotozoan-parasites (Theileria ovis and Babesia ovis) and bacteria in ticks and blood from small ruminants in Northern Algeria. (February 2017) - Aouadi, Atef; Leulmi, Hamza; Boucheikhchoukh, Mehdi; Benakhla, Ahmed; Raoult, Didier; Parola, Philippe
Highlights: This paper expand knowledge about the repertoire of tick-borne microorganisms present in ectoparasites and/or the blood of small ruminants in Algeria. The first molecular detection of Theileria ovis, Babesia ovis in sheep and goats and ticks in Algeria. The first direct evidence of Borrelia theileri, Anaplasma ovis and Coxiella burnetii in sheep and goats and ticks in Algeria. Abstract: Using qPCR, standard PCR and/or sequencing, we investigated the presence of tick-associated microorganisms in ticks and blood from sheep and goats from Souk Ahras, Algeria. Borrelia theileri, was detected in (7/120, 5.8%) blood from sheep and (13/120, 10.8%) goats. Anaplasma ovis was screened in (38/73, 52%) Rhipicephalus bursa and (5/22, 22.7%) R. turanicus and in (74/120, 61.7%), (65/120, 54.2%) blood of sheep and goats respectively. Coxiella burnetii tested positive in R. bursa (4/73, 5.5%) and (7/120, 5.8%) blood of sheep and (2/120, 1.7%) goats. Theileria ovis was detected in (50/147, 34%) R. bursa and (3/22, 13.6%) R. turanicus and in (64/120, 53.3%) blood of sheep and (25/120, 20.8%) goats. Babesia ovis was screened positive in (23/147, 15.6%) R. bursa and (7/48, 14.6%) R. turanicus . Our findings expand knowledge about the repertoire of tick-borne microorganisms present in ectoparasites and/or the blood of small ruminants in Algeria.